Using the TPB model to determine factors affecting e-learning adoption in Jordanian higher education - Altawalbeh, Manal; Al-Mughrabi, Ayat Mohammad (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this study was to use the TPB Model to identify the variables influencing the adoption of e-learning in Jordanian higher education. The worldwide trend towards e-learning has resulted in considerable operational changes for Jordan’s higher education institutions (HEI). There were 850 students in the sample. The proportionate stratified random sample approach was used to select them at random from the general population. To gather information, a questionnaire was developed. The tool’s validity and dependability were guaranteed. An analysis of regression was done to evaluate the associations between the constructs. The findings demonstrated that attitude (AT), subjective norm (SN), and perceived behavioral control (PBC) significantly influence behavioral intention (BI). In light of the results, the researchers proposed rerunning the study in various contexts (such as additional Jordanian universities) in order to assess the validity of the enlarged research model. The sample could comprise both actual users of online learning and non-users in order to compare the findings and ascertain why e-learning is being adopted or not. The study’s findings provide a framework for understanding the factors influencing faculty members’ and students’ intents to use e-learning at Jordanian institutions, which can be useful for students, policymakers, and system developers.